DEVELOPING ENGLISH TEACHING MATERIALS FOR ACCOUNTING STUDENTS: AN ESP APPROACH - Novrika Nartiningrum; Arif Nugroho (PROJECT (Professional Journal of English Education), 2020)
The contextualization of teaching materials with learners’ needs is an absolute demand to achieve the success of a language learning. For this purpose, the present study aims to develop representative English materials for accounting students at IAIN Surakarta. Drawing on a research and development, this study was based on procedures adapted from Latief (2014), which followed several stages (1) need analysis; (2) prototype development; (3) experts validation; (4) field test/try-out; (5) product revision; and (6) dissemination and implementation. A questionnaire, focus group discussion, and semi-structured interview were employed to gather the data on students’ needs and material feedbacks from 147 accounting students, 3 English teachers, and the head of accounting department at IAIN Surakarta. The results revealed that the students needed English materials that were closely related to accounting and business field. This study also resulted in a developed modul consisting of eight units, each unit presents reading, speaking, and writing skills that were contextualized with the students’ needs. These results have filled the existing gap of providing representative materials to assist the students to develop their language skills in accounting and business environment.Keywords: English for Accounting, Material Development, Need Analysis, Research and Development